Creative destruction caused by the cosmetic products; A false signal - Syeda Farah Batool; Yusra Saleem; Stephen Riaz; Sadaf Ahmed (International Journal on Women Empowerment, 2019)
Background: The Cosmetic industry now dominates the global standards of beauty due to the unreal definition of an ideal appearance. Advertising companies are playing with the human psychology and have displayed such a perfect body image that now people feel disappointed with their natural appearance and tend to opt the cosmetic products for a perfect look. The purpose of this research was to explore the attitude and opinion of females regarding cosmetic products and to evaluate the factors of self-esteem, makeup involvement and makeup satisfaction. Methodology: An observational cross-sectional study was conducted from September to November 2018. A total of 107 females from diverse affiliations were enrolled in the study. Data was collected using a structured questionnaire inquiring the respondent’s demographic details, together with the information regarding cosmetics use, preferences and perceptions etc. Five-point Likert scale was used for rating the level of happiness/satisfaction with and without makeup and questions pertaining to the responder’s perception of self-image and makeup involvement. The collected data was analyzed using SPSS Version 22.0. Results: The mean age of the respondents was 21.5±4.68 years and the age when they first started wearing makeup was 17.14±2.87 years. Based on the results, 42.1% females were very happy with their natural face features without makeup while 55.1% preferred applying makeup. Moreover, latest trends (64.8%), discounts (17.6%), advertisements (16.7%) and morning shows (3.7%) were among the major sources capturing females for cosmetic purchase. 57.0% were involved in cosmetic purchase monthly and 30.8% were those spending 1000 to 2000 PKR per month on cosmetic products. Women mostly preferred cosmetic products for facial care (43.9%) and to improve self-image (28.0%). Although 55.1% of them preferred wearing no makeup to school or work while 39.3% would wear little makeup. Regarding the cosmetic use and purpose, 41.1% females strongly agreed to the fact that they feel good when their makeup is good. Moreover, 15.0% voted for confidence and desirability and 13.1% agreed that it is mainly used for hiding flaws. Conclusion: Although equal number of women reported loving their natural features without makeup as compared to those preferring makeup but it might be indicative of personal bias as it is evident that the women today wants to be seen confident and attractive. The unbreakable trend set by cosmetic companies and media marketers completely influenced the society and for fulfilling the desires for ideality we reach out to hide all odds.